The diagnostic performance of ultrasound elastography for biliary atresia: A meta-analysis - Dong, Bingtian; Weng, Zongjie; Lyu, Guorong; Yang, Xiaocen; Wang, Huaming (Frontiers in Public Health, 2022)
Background Biliary atresia (BA) is a severe inflammatory obliterative cholangiopathy of infancy that requires early diagnosis and prompt surgical intervention. In this study, we aimed to obtain comprehensive evidence on the diagnostic performance of liver stiffness measurement by ultrasound elastography in the detection of BA through a meta-analysis. Methods The PubMed, EMBASE, Cochrane Library, and Web of Science databases were searched for studies that investigated the diagnostic performance of ultrasound elastography in the detection of BA up to January 10, 2022. In this study, in order to summarize the diagnostic performance of ultrasound elastography, the summary receiver operating characteristic (SROC) modeling was constructed. Heterogeneity was estimated with the I2 statistic. Multiple subgroup analyses were also performed. Results Fourteen studies from eleven articles, including 774 BA patients, 850 non-BA patients, and 173 controls were included in the present meta-analysis. The summary sensitivity and specificity of ultrasound elastography for liver stiffness were 85% [95% confidence interval (CI): 79–89%] and 82% (95% CI: 73–88%) with the I2 value of 82.90 and 84.33%, respectively. The area under the SROC curve (AUROC) using ultrasound elastography for diagnosing BA was 0.90 (95% CI: 0.87–0.92). In addition, a subgroup analysis of 9 two-dimensional shear wave elastography studies was also performed. Subgroup analysis revealed that the summary sensitivity and specificity were 85% (95% CI: 77–91%) and 79% (95% CI: 71–86%), respectively, and the summary AUROC was 0.89 (95% CI: 0.86–0.92). Conclusions Ultrasound elastography exhibits good diagnostic accuracy for BA and can be served as a non-invasive tool to facilitate the differential diagnosis of BA.